2020
DOI: 10.1007/978-3-030-58475-7_46
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Based Software Diversification for Efficient Mitigation of Code-Reuse Attacks

Abstract: Modern software deployment process produces software that is uniform, and hence vulnerable to large-scale code-reuse attacks. Compiler-based diversification improves the resilience and security of software systems by automatically generating different assembly code versions of a given program. Existing techniques are efficient but do not have a precise control over the quality of the generated code variants.This paper introduces Diversity by Construction (DivCon), a constraint-based compiler approach to softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…• an experimental demonstration of the effectiveness of LNS at generating highly diverse solutions efficiently; • the evaluation of DivCon on a wide set of benchmarks of different sizes, including large functions of up to 500 instructions; • a quantitative assessment of the technique to mitigate code-reuse attacks effectively, while preserving high code quality; and • a publicly available tool for constraint-based software diversification 1 . This paper extends our previous work (Tsoupidi, Castañeda Lozano, & Baudry, 2020). We extend our investigation of LNS for code diversification with Decomposition-based Large Neighborhood Search (DLNS) (Sections 3.2, 4.2, and 4.4), a specific LNS-based approach for generating diverse solutions for larger programs.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…• an experimental demonstration of the effectiveness of LNS at generating highly diverse solutions efficiently; • the evaluation of DivCon on a wide set of benchmarks of different sizes, including large functions of up to 500 instructions; • a quantitative assessment of the technique to mitigate code-reuse attacks effectively, while preserving high code quality; and • a publicly available tool for constraint-based software diversification 1 . This paper extends our previous work (Tsoupidi, Castañeda Lozano, & Baudry, 2020). We extend our investigation of LNS for code diversification with Decomposition-based Large Neighborhood Search (DLNS) (Sections 3.2, 4.2, and 4.4), a specific LNS-based approach for generating diverse solutions for larger programs.…”
Section: Introductionsupporting
confidence: 52%
“…The relax rate is selected empirically based on preliminary experiments (Appendix A). Note that in our previous paper (Tsoupidi et al, 2020), the best relax rate on a different benchmark set was found to be 70%. This suggests that the optimal relax rate depends on the properties of the program under compilation, where the number of instructions appears to be a significant factor.…”
Section: Methodsmentioning
confidence: 82%
“…This lack of clarity means that designers of bug-finding tools lack a general test for deciding whether (or in what context) a given bug pattern is appropriate. The impact of this question extends beyond bug finding: as we make progress in synthesising code [20], in mining and applying bug fixes [21], and in other strategies for manually or automatically evolving software [22], we need to ask whether these systems can introduce new bugs.…”
Section: Introductionmentioning
confidence: 99%